Крановый гусеничный движитель. Теория и практика преодоления препятствий - Водченко, О. П. (НТУ "ХПИ", 2010)
У статті розглянуто кранове гусеничне шасі з пружною підвіскою опорних котків. Докладно розглянуто рівняння безрозривності гусеничного обводу. На основі цього рівняння одержані узагальнені залежності процесу переїзду колоди. Теорія стверджена експериментальними дослідженнями.

In article it is considered crane the caterpillar chassis with an elastic suspension bracket of basic Roller. The equation of indissolubility of caterpillar contour is in detail considered. On the basis of this equation the generalized dependences of process of moving of a log are received. The theory is confirmed by tests.
Keywords: гусеничные шасси; крановые системы; гусеничный обвод; уравнение неразрывности